Unravelling the molecular mechanisms of HIV associated neurocognitive disorders through mass spectrometry-based proteomics - Gurwitz, Kim Tamara (Division of Medical Biochemistry, 2017)
A significant proportion of human immunodeficiency virus type 1 (HIV)-positive individuals are affected by the cognitive, motor and behavioural dysfunction that characterises HIV associated neurocognitive disorders. While the molecular aetiology of this important HIV complication remains largely uncharacterised, HIV transactivator of transcription (HIV-Tat) has been identified as a plausible aetiological cause. Here we have used mass spectrometry-based discovery proteomics to identify the quantitative, cell-wide changes that occur when non-transformed, differentiated human neurons are treated with HIV-Tat over time, as a novel cell culture model representing the initial progression of HIV associated neurocognitive disorders, and as a means to identify putative biomarkers for the illness. We found that our stem cell-based model system displayed morphological and functional neuronal properties and using a Q-Exactive mass spectrometer, we identified over 4000 protein groups (FDR < 0.01) in this system with 131,118 and 45 protein groups differentially expressed at 6, 24 and 48 hours post treatment, respectively. We found changes to the gene expression machinery (nucleic acid binding proteins), which suggests that HIV-Tat is involved in preparing the host cell for altered transcriptional and translational activity. We also found cytoskeletal dysregulation in response to HIV-Tat treatment. The 24-hour time point of the time course experiment was largely corroborated with a repeat experiment. A repeat of the entire time course experiment at a lower cell confluence showed that the effect of HIV-Tat treatment to the gene expression machinery was unchanged by cell confluence, while the effect to cytoskeletal proteins upon HIV-Tat treatment was present, but less prominent, in lower cell confluence samples. We hypothesise that the gene-expression-machinery effect may be a biphasic response. We further hypothesise that cytoskeletal dysregulation may form part of the molecular mechanism responsible for synaptic injury - as the cytoskeleton is crucial for synapse development and maintenance - and may contribute to memory impairment in HIV associated neurocognitive disorder patients.